2020
DOI: 10.1001/jamaophthalmol.2020.0006
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Effect of Intraocular Lens vs Contact Lens Correction on Visual Acuity After Cataract Surgery During Infancy

Abstract: IMPORTANCEAlthough intraocular lenses (IOLs) are often implanted in children, little is known whether primary IOL implantation or aphakia and contact lens correction results in better long-term visual outcomes after unilateral cataract surgery during infancy.OBJECTIVE To compare long-term visual outcomes with contact lens vs IOL correction following unilateral cataract surgery during infancy. DESIGN, SETTING, AND PARTICIPANTSThis multicenter randomized clinical trial enrolled 114 infants with a unilateral cong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 31 publications
0
77
0
Order By: Relevance
“…Vasavada et al reported that in their study, more infants in primary IOL group had documentable VA compared with aphakia group during early postoperative follow‐up, and this trend continued until age 5, namely the visual rehabilitation would be faster in primary IOL group, especially in early postoperative follow‐up 22 . However, in the IATS study, the VA was similar in the IOL group and the contact lens group at 1‐year, 6 4.5‐year 11 and 10.5‐year follow‐ups, 32 which could be explained by better compliance with wearing of contact lenses, spectacles and patches in the aphakia group. The IATS offered free contact lenses, spectacles and patches for the enrolled subjects thus, there were fewer financial barriers to adhering to the postoperative follow‐up protocol 41,42 .…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Vasavada et al reported that in their study, more infants in primary IOL group had documentable VA compared with aphakia group during early postoperative follow‐up, and this trend continued until age 5, namely the visual rehabilitation would be faster in primary IOL group, especially in early postoperative follow‐up 22 . However, in the IATS study, the VA was similar in the IOL group and the contact lens group at 1‐year, 6 4.5‐year 11 and 10.5‐year follow‐ups, 32 which could be explained by better compliance with wearing of contact lenses, spectacles and patches in the aphakia group. The IATS offered free contact lenses, spectacles and patches for the enrolled subjects thus, there were fewer financial barriers to adhering to the postoperative follow‐up protocol 41,42 .…”
Section: Discussionmentioning
confidence: 90%
“…The IATS reported the randomisation process and intervention deviation, and had no selective reporting and outcome data missing 11,30‐32 . The study of Qian 38 did not describe the approach of random sequence generation and potential intervention deviation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Common complications of childhood cataract surgery include PCO (more precisely, Elschnig pearls proliferation and secondary membranes), despite posterior capsulorhexis (Figure 1E), aphakic or pseudophakic glaucoma, uveitis, pupil displacement and IOL decentration (5). Long-term visual outcome at 10 years and complication rates at 5 years seems similar after cataract extraction with or without primary IOL implantation (27,28).…”
Section: Cataract Diagnosis and Managementmentioning
confidence: 95%
“…Congenital cataracts are the leading cause of preventable blindness in children [1]. Well-timed surgical intervention may prevent deprivation amblyopia and result in good visual prognosis [2]. Despite advancements in the estimation of refractive outcome, surgical management, and the postoperative control of myopic shift and rehabilitation [3,4], late adverse events may jeopardize the result of the initial treatment [5,6].…”
mentioning
confidence: 99%